Introduction to cost-effective energy-efficient building retrofitting - Pacheco-Torgal, F. (2017)
This chapter starts with a brief review of the unsustainability of energy production, which is the main responsible for global greenhouse gas (GHG) emissions and also on the importance of energy efficiency to abate global GHG emissions. A short look at building energy efficiency and energy retrofitting within the European building stock and the EU legislation is given. A short analysis of several incentives that are available for financing energy retrofitting in Europe is presented. Social aspects regarding energy retrofitting are reviewed. A book outline is presented.